2015
DOI: 10.1590/0103-9016-2014-0312
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-induced alterations in the photosynthetic performance and resistance of rice plants infected with Bipolaris oryzae

Abstract: Brown spot (BS), caused by the fungus Bipolaris oryzae, is one of the most important diseases contracted by rice. We investigated the effect of magnesium (Mg) on the development of BS, caused by Bipolaris oryzae, and the effects of disease development on the photosynthetic performance of rice (Oryza sativa L.) plants (cv. Metica-1) grown in nutrient solutions containing 0.25 or 4.0 mM of Mg. Assessments of BS severity, leaf Mg and pigment concentrations (total chlorophylls and carotenoids), were carried out at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…(2013) , who reported that a deficiency in maize plants increased their susceptibility to heat stress. Moreira et al. (2015) established that a higher concentration of Mg 2+ results in reduced disease severity and improved photosynthesis.…”
Section: Impact Of Magnesium On Crop Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…(2013) , who reported that a deficiency in maize plants increased their susceptibility to heat stress. Moreira et al. (2015) established that a higher concentration of Mg 2+ results in reduced disease severity and improved photosynthesis.…”
Section: Impact Of Magnesium On Crop Developmentmentioning
confidence: 99%
“…The importance of Mg 2+ is further emphasized by Mengutay et al (2013), who reported that a deficiency in maize plants increased their susceptibility to heat stress. Moreira et al (2015) established that a higher concentration of Mg 2+ results in reduced disease severity and improved photosynthesis. Rajitha et al (2019) documented Mg 2+ positive influence on groundnuts, while Tan et al (2000) acknowledged its role in optimizing the yields of sweet potatoes, sugarcane, and various vegetables.…”
Section: Effects Of Magnesium On Crop Qualitymentioning
confidence: 99%
“…Calcium appears to be especially effective for post-harvest treatments against gray mould caused by Botrytis cinerea [209,210], whereas magnesium showed inconsistent results in controlling diseases [211]. Further ad hoc studies should be performed to determine the potential beneficial effects [212].…”
Section: Nutrition Managementmentioning
confidence: 99%